Role reflections of police reservists: a study of volunteer reserve officers in Malaysia. Issue 6 (3rd December 2018) - Cheah, Phaik Kin; Unnithan, N. Prabha; Suppiah, Suresh
Abstract : Purpose: The purpose of this paper is to investigate the work roles of the Royal Malaysia Police Volunteer Reserve officers. Design/methodology/approach: A grounded theory approach was utilized for the generation and analysis of the data. Data were collected through interviews, observations and follow-ups. Semi-structured interviews were conducted with 20 male and female volunteer reserve officers and 5 regular police officers aged between 24 and 58 years of mixed socioeconomic backgrounds, ethnicities and ranking in the Royal Malaysia Police force. Two civilian respondents (spouses of the Police Volunteer Reserve officers) were also interviewed for this study for the purpose of theory sampling. Findings: The data were analyzed qualitatively resulting in a model of Royal Malaysia Police Volunteer Reserve officer roles consisting of four orientations. Research limitations/implications: Study outcomes are discussed theoretically and administratively. The four role orientations identified will assist researchers studying police reserve volunteerism. Practical implications: Study outcomes allow administrators to utilize and deploy police reservists in consonance with the four role orientations identified. Social implications: This study provides insight into how police reservists conceive of and execute their roles as they negotiate them in relation to the regular police officers they work with and the public from which they are drawn. Originality/value: This is the first study of police volunteerism in Malaysia.